Exergoenvironmental evaluation of a cement manufacturing process in Nigeria (2013)
The Cement manufacturing process is an energy intensive and environmentally impacting process. In this study, an exergoenvironmental evaluation is conducted on a wet process, gas - fired 1.3 million tone capacity cement plant in Nigeria, to assess the ecological impact of its production process by revealing the extent to which each major component of the production process is responsible for the overall environmental impact and identify the sources of the impact. Exergoenvironmental evaluation consists of three major steps. The first step involves a detailed exergy analysis of the production system under consideration using the input - output energy analysis method; in the second step, the required values of the environmental impact are determined by applying the ECO - 99 life cycle assessment method. In the third step the environmental impacts are assigned to the exergy streams in the process. Subsequently, exergoenvironmental variables are calculated and the exergoenvironmental evaluation is carried out. . Based on a 70% utilization capacity, embodied energy intensity of 7.07GJ/t and overall exergic efficiency of 0.55; the exergoenvironmental evaluation shows that the major process components impacting the environment were the kiln and limestone extraction processes. The study also showed that exergy destruction occasioned by process and combustion emissions in the kiln is the major source of environmental hazards in the process. With an overall environmental factor of 20.3% for the plant, the study concludes that the environmental hazards are mainly due to system irreversibilities in the process and not the related components environmental factor.